Design and animation of automated alternative solar water heater system at the BRAC University roof top by using solid works and implement the controller using GAL technology - Chowdhury, Ahasanul Haque (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electronics and Communication Engineering, 2012.